The Effect of Hydrological Connectivity on Fish Assemblages in a Floodplain System From the South-East Gulf of California, Mexico - Amezcua, Felipe; Rajnohova, Jana; Flores-de-Santiago, Francisco; Flores-Verdugo, Francisco; Amezcua-Linares, Felipe (Frontiers in Marine Science, 2019)
The effect of hydrological connectivity of the fish assemblages was assessed on a floodplain in the SE Gulf of California, Mexico using a Before–After Control-Impact (BACI) design. Community structure attributes of species abundance, biomass, richness, diversity, and differences in the structure of fish assemblages were compared between two periods (January to June in 2011 and 2015) and two flood plains, one designated as the control zone which was divided by a road, and another one designated as the treatment zone which from January – June 2011 was divided by a road, and then sampled from January - June 2015, as the site was rehabilitated by removing the road in the year 2012. Fish were sampled at monthly intervals using a seine net at different stations in both floodplains. A total of 7024 organisms, comprising of 14 species belonging to 11 families, were analysed. In the control zone during both periods and in the treatment zone before removal of the road Poecilia butleri was the most abundant species and two exotic species (Tilapia) accounted for more than 95% of the total biomass. After the removal of the road in the treatment zone Poeciliopsis latidens was the most abundant species and the relative biomass of both species of tilapia decreased to 85%, but was still the most important in terms of biomass. However, richness and diversity were higher and the structure of the fish assemblages was different in the treatment zone after the road was removed, due to the presence of species with estuarine and marine affinity in this zone and period. Our results indicate that hydrological connectivity proved to be a key factor influencing the fish composition and abundance in the floodplain system in the region. Hence, a better hydrological connectivity implied higher abundance and diversity, likely related to an increase in the habitat complexity. The priority in the management of the ecological functioning of the floodplain system should be set on minimising the modifications of the natural flow and thus avoiding the changes on the fish biota.